The Subjects of Transnational Business and the Processes of Global Economic Governance - Sergey A. Afontsev (Контуры глобальных трансформаций: политика, экономика, право, 2018)
In recent decades, transnational business actors have substantially strengthened their role in global economic governance. Although this trend became less pronounced after the global crisis of 2008–2009, it was by no means reversed. With multinational companies (including those from developing markets) increasing scale and scope of their operation and national governments competing for foreign direct investment (FDI) as a development resource, both official and public-private economic governance mechanisms shape their agenda with a reference to transnational business interests. As a result, FDI promotion policies prevailed in post-crisis years, in contrast with a remarkable growth of protectionism in international trade. At the same time, as the case of economic sanctions shows, with increased tensions in international relations business interests are readily sacrificed, and thus far transnational business actors have no reliable tools to change the situation.